Macrophage Function in the Pathogenesis of Non-alcoholic Fatty Liver Disease: The Mac Attack - Oates, Jarren R.; McKell, Melanie C.; Moreno-Fernandez, Maria E.; Damen, Michelle S. M. A.; Deepe, George S.; Qualls, Joseph E.; Divanovic, Senad (Frontiers in Immunology, 2019)
Obesity is a prevalent predisposing factor to non-alcoholic fatty liver disease (NAFLD), the most common chronic liver disease in the developed world. NAFLD spectrum of disease involves progression from steatosis (NAFL), to steatohepatitis (NASH), cirrhosis and hepatocellular carcinoma (HCC). Despite clinical and public health significance, current FDA approved therapies for NAFLD are lacking in part due to insufficient understanding of pathogenic mechanisms driving disease progression. The etiology of NAFLD is multifactorial. The induction of both systemic and tissue inflammation consequential of skewed immune cell metabolic state, polarization, tissue recruitment and activation are central to NAFLD progression. Here, we review the current understanding of the above stated cellular and molecular processes that govern macrophage contribution to NAFLD pathogenesis and how adipose tissue and liver crosstalk modulates macrophage function. Notably, the manipulation of such events may lead to the development of new therapies for NAFLD.